NK Cell Anti-Tumor Surveillance in a Myeloid Cell-Shaped Environment - Russo, Eleonora; Laffranchi, Mattia; Tomaipitinca, Luana; Del Prete, Annalisa; Santoni, Angela; Sozzani, Silvano; Bernardini, Giovanni (Frontiers in Immunology, 2021)
NK cells are innate lymphoid cells endowed with cytotoxic capacity that play key roles in the immune surveillance of tumors. Increasing evidence indicates that NK cells anti-tumor response is shaped by bidirectional interactions with myeloid cell subsets such as dendritic cells (DCs) and macrophages. DC-NK cell crosstalk in the tumor microenvironment (TME) strongly impacts on the overall NK cell anti-tumor response as DCs can affect NK cell survival and optimal activation while, in turn, NK cells can stimulate DCs survival, maturation and tumor infiltration through the release of soluble factors. Similarly, macrophages can either shape NK cell differentiation and function by expressing activating receptor ligands and/or cytokines, or they can contribute to the establishment of an immune-suppressive microenvironment through the expression and secretion of molecules that ultimately lead to NK cell inhibition. Consequently, the exploitation of NK cell interaction with DCs or macrophages in the tumor context may result in an improvement of efficacy of immunotherapeutic approaches.